Design approach for Revitalization of The Cultural Heritage Johar Market Area - Saraswati, Ratri Septina (Science and Technology Research Centre, Universitas PGRI Semarang, 2020)
Johar Market and surrounding area as historical value suffered decaying process during the economic growth of that area. The mismanagement and uncontrolled growth caused high density of stall, break in public spaces such as roads and open spaces (aloon aloon). The Johar Market fired in 2015 Based on this tragedy, the Semarang City Government revitalized Johar Market also the surrounding area as a modern economic center that still adheres to the principle of preserving cultural heritage. Pasar Johar experienced a major fire that not only damaged the market building, but also the surrounding area. This article is part of the results of research conducted for Masterplan for the Revitalization of the Johar Cultural Heritage Area in 2016 that initiated by the Semarang City Planning Agency. Revitalization process include analysis of reorganizing the original imaginary axis between Johar and the Great Mosque Kauman. Another axis between former Regent House and the Dutch Government. Rebuilt the open space aloon aloon as public space, and revitalizing the community kampong around the area. The benefits of this plan should be give positive impact for the public community, the merchants, and Semarang as the valuable historical part of the city.